Pendekatan dalam pengembangan kurikulum - Alfarizi, Ahmad Muhammad (Maliki Interdisciplinary Journal, 2024)
In the process of learning activities, there is something that is needed, namely a curriculum, curriculum is a set of plans and also settings and targets as guidelines for achieving the results of the teaching and learning process. The curriculum is a supporting tool for achieving dynamic educational goals so that the curriculum itself must and needs to be developed in accordance with the development of the times and technology that exists at that time. Therefore, in the educational process curriculum development is very important, where quality in education is not only processing learning materials but is more focused on improving the quality of education itself.